FREE FAT IN MILK AND CHEESE PRODUCTS: INFLUENCE ON QUALITY - O. V. Lepilkina; I. V. Loginova; O. G. Kashnikova (Пищевые системы, 2020)
The theoretical and practical aspects of the formation of free fat in milk, cheese and cheese products with vegetable fats are considered. The amount of free fat in milk depends on the integrity of the fat globules membranes, which are affected by: ineffective emulsification of fat during the synthesis of milk in the cow’s udder (authentic fat) and physic-mechanical factors in the milk processing after milking (destabilized fat). Free fat, primarily subjected to oxidative processes and lipolysis, reduces the quality and ability to store milk. For cheese products, the presence of free fat, available for lipolysis and oxidation, is a prerequisite for obtaining high-quality products. Characteristics of the production of cheese products with vegetable fats, providing for the preliminary emulsification of vegetable fat in skim milk, contribute to the formation of denser membranes on the surface of fat globules, consisting mainly of casein micelles and whey proteins. This is the reason for the formation of a more closed structure of the fat phase with low availability of fat for enzymes and oxidizing agents. The low availability of fat in the structure of cheese products with vegetable fats is one of the factors that worsen their organoleptic characteristics. In order to increase the amount of available fat in the production of cheese products with vegetable fats, it is advisable to use additional enzyme preparations or cultures of microorganisms that activate proteolysis and lipolysis.